2009
DOI: 10.1590/s1516-14392009000400022
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies of osteoblasts response onto zinc aluminate ceramic films

Abstract: Zinc based or doped ceramics have shown to be capable of increasing osteoblasts proliferation, biomineralization and bone formation. However, studies regarding the biological applications processes in ZnAl 2 O 4 ceramic films are very scarce. For this reason, the objective of this in vitro study was to investigate the response of osteoblasts cells cultured onto ZnAl 2 O 4 films. Our results showed a good biological response related to attachment and viability, with good cell morphology attached to the semi-sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It was recently demonstrated that zinc‐based or doped ceramics are able to increase osteoblasts proliferation, biomineralization, and bone formation 18. The ZnAl 2 O 4 spinel compound showed a good biological response with regards to attachment and viability, with good cell morphology adhered to the semi‐spherical grains of the ceramic 19, 20. Nanoporous spinel may therefore be easily integrated for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that zinc‐based or doped ceramics are able to increase osteoblasts proliferation, biomineralization, and bone formation 18. The ZnAl 2 O 4 spinel compound showed a good biological response with regards to attachment and viability, with good cell morphology adhered to the semi‐spherical grains of the ceramic 19, 20. Nanoporous spinel may therefore be easily integrated for such applications.…”
Section: Introductionmentioning
confidence: 99%